Acute polymorphic psychosis: An interesting case report. (13th April 2021) - Mari, V.; Georgiadi, A.; Maris, A.; Gkolia, I.
Abstract : Introduction: Acute Polymorphic Psychotic Disorder is a psychotic disorder with an acute onset, presenting thought and perception disorders variable into hours. Often, an emotional fluctuation is present and it may have a sudden onset and a rapid remission. Objectives: The review's objective is to manifest acute polymorhic psychotic disorders and possible effective medical interventions. Methods: The current case concerns a 52-year old mother of 4 children with the manifestation of acute polymorphic psychotic disorder with a background of a stressful factor. The patient was involuntarily hospitalized in the Psychiatric Hospital of Thessaloniki from 04/01/ 2019 -21/ 01/2019 due to disorganization and acute confusing condition within the last 9 days. Delusional ideas of religious content were first observed, which alternated with ideas of greatness and then persecution, association and self-denial. She also presented auditory hallucinations while there was a fluctuation of emotion from excessive euphoria to depression. The patient had no previous hospitalization in a psychiatric clinic, however, 7 months ago she experienced another acute psychotic epeisode, while at the age of 17 and under the influence of intense stress, she described mood disorders. Results: The current symptoms subsided after one week from the day of admission. During her hospitalization, a brain CT was performed without presence of pathological findings. Initially, her medication included i.m. haloperidol 15mg / ml daily, followed by a change to per os paliperidone 9mg daily. Conclusions: Her mental status was improved, with no disturbances of consciousness noted and she was discharged on paliperidone as home medication. Disclosure: No significant relationships.